2021
DOI: 10.3390/ijms22042207
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of STCH and Stress-Inducible Hsp70 on the Stability and Maturation of NKCC2

Abstract: Mutations in the Na-K-2Cl co-transporter NKCC2 lead to type I Bartter syndrome, a life-threatening kidney disease. We previously showed that export from the ER constitutes the limiting step in NKCC2 maturation and cell surface expression. Yet, the molecular mechanisms involved in this process remain obscure. Here, we report the identification of chaperone stress 70 protein (STCH) and the stress-inducible heat shock protein 70 (Hsp70), as two novel binding partners of the ER-resident form of NKCC2. STCH knock-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 73 publications
(159 reference statements)
1
46
0
Order By: Relevance
“…The above findings strongly suggest that in cells expressing NKCC2 variants, the defect in the cotransporter maturation arises from ER retention and associated degradation. Given that NKCC2 protein is modified by N ‐linked glycosylation (Benziane et al, 2007) and that several studies have shown that mannose trimming is required for ER‐associated proteasomal degradation of glycoproteins (Bakhos‐Douaihy et al, 2021; Tokunaga et al, 2000; Wang et al, 2011), we compared the effect of MG132 to that of kifunensine on NKCC2 variants. Of note, kifunensine is commonly used to inhibits α‐mannosidases I (including ER mannosidase I and ER Degradation Enhancing Alpha‐Mannosidase Like Protein [EDEM]) that are required for the early steps of ERAD misfolded glycoprotein recognition (Bakhos‐Douaihy et al, 2021; Gong et al, 2005; Groisman et al, 2011; Tokunaga et al, 2000; Wang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The above findings strongly suggest that in cells expressing NKCC2 variants, the defect in the cotransporter maturation arises from ER retention and associated degradation. Given that NKCC2 protein is modified by N ‐linked glycosylation (Benziane et al, 2007) and that several studies have shown that mannose trimming is required for ER‐associated proteasomal degradation of glycoproteins (Bakhos‐Douaihy et al, 2021; Tokunaga et al, 2000; Wang et al, 2011), we compared the effect of MG132 to that of kifunensine on NKCC2 variants. Of note, kifunensine is commonly used to inhibits α‐mannosidases I (including ER mannosidase I and ER Degradation Enhancing Alpha‐Mannosidase Like Protein [EDEM]) that are required for the early steps of ERAD misfolded glycoprotein recognition (Bakhos‐Douaihy et al, 2021; Gong et al, 2005; Groisman et al, 2011; Tokunaga et al, 2000; Wang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(a) Effect of MG132 on protein levels of wild‐type and mutants NKCC2 proteins in HEK cells. HEK cells transiently transfected with wild‐type NKCC2 or NKCC2 mutants were treated without (C) or with 2 µM MG132 (M) for 6 for 12 h prior cell lysis, as previously described (Bakhos‐Douaihy et al, 2021). The cell lysates were subjected to SDS‐PAGE and immunoblotted with anti‐Myc antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second postulates that the mutations in MAGED2 prevent sufficient concentrations of cyclic adenosine monophosphate (cAMP) for the correct function of the antidiuretic hormone (ADH), causing the mislocalization of the channels [ 70 ]. It is essential to bear in mind that ERAD, lysosomal degradation and the specific ubiquitination of unfolded and immature NCC and NKCC2 have also been widely described as key mechanisms of protein expression and localization [ 72 , 73 , 74 , 75 ], for which further study of Bartter’s disease type 5 will contribute to a greater understanding of these fundamental processes. Similarly, the presence of mutations in the MAGED2 gene could explain the cases of idiopathic polyhydramnios and unresolved prenatal tubulopathies [ 76 ].…”
Section: Molecular Basis and Clinical Features Of The Diseasesmentioning
confidence: 99%